Electromagnetic force generation for dynamic modal testing applications - Norlida, Jamil (2015)
Milling is one of the most common manufacturing processes for manufacturing sectors. However, high speed machining problems notably tool chatter in function of both spindle speed and depth of cut. Thus, many researchers found that to detect or reduce chatter is by determining its dynamic characteristics such as natural frequency, damping ratio, mode shapes and frequency response functions (FRFs). To predict the stability of the cutting tool system, modal testing using impact hammer is required to gain cutting tool‟s dynamic properties and FRFs. However, this method is suited well for non-rotating tools, but cannot be used to identify the dynamic of a rotating spindle. Thus, a non-contacting Electromagnetic Actuator (EMA) was designed and guided by analytical and numerical method. The geometry was designed using magnetic circuit analysis (MCA) and generalized machined theory (GMT) before FE analysis was conducted using Magnetostatic-Ansys software. Next, impact hammer and EMA were used as a contacting and non-contacting exciter respectively at a conventional milling machine in order to determine the FRFs and dynamic properties of milling tool with amplitude and speed dependencies including comparing with static FRFs. Subsequently, dynamic characteristic and FRFs obtained using non-contacting EMA later used to establish Stability Lobe Diagram (SLD). The magnetostatic analysis result has shown the magnetic flux produced were stable and controllable. Besides, the study has shown a good agreement between impact hammer and EMA with 8.74 percent of percentage error. The error between EMA and impact hammer may have resulted from inconsistencies with impact hammer testing. It should be noted that the EMA applied a distributed load to the tool instead of a point load. Furthermore, the variability in frequency values from FEA is probably due to differences in the boundary conditions of the milling machine. The SLD also showed an improvement which up to 5 percent for depth of cut at lower spindle speed. Thus, EMA produced can determine dynamic properties yet for the purpose of chatter prediction. In conclusion, this research had successfully design and analyzes an EMA that can determine dynamic properties and SLD to increase MRR and production rate, by generating force applies for static and dynamic modal testing.